THE KEY ASPECTS OF MANAGING THE ECONOMIC POTENTIAL OF CONSTRUCTION INDUSTRY ENTERPRISES OF UZBEKISTAN IN THE CONTEXT OF DIGITALIZATION - Badirov D. A. (Modern American Journals, 2025)
There are various aspects of the construction industry's economic potential. The effective management of economic potential is crucial to navigate this changing landscape and ensure sustainable growth and profitability. There is a need to study the key aspects of managing the economic potential of construction industry enterprises in the context of digitalization. The main aspects of economic potential are: resource efficiency, innovation potential, and labor productivity. In the era of digitalization, there is a need to approach these problems from a different perspective, using like a BIM (Building Information Modeling). BIM is a digital process used in construction and architecture to create and manage all the information related to a building project throughout its entire lifecycle, from design and construction to operation and maintenance. Also it includes resource efficiency, innovation potential and labor productivity.
Keywords: Construction industry, resource efficiency, innovation potential, labor productivity, digital technology, digital gap, management, BIM.